PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN LKS TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Mustika, Helma; Fitri, Ramadhani; Astuti, Puji; Fadhilah Hartati, Yunisa; Ningsih, Sri Yunita; Oktiviani, Selvi Sri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This research originates from the results of a preliminary study at SMP Negeri 3 Pasir Penyu, grade VIII students. This study aims to determine the effect of LKS- Assisted Discovery Learning Model on the Mathematical Concept Understanding Ability of Class VIII. The type of this research is True experimental, with the design of The Randomized Subject Posttest Only Control Group. The sampling technique in this study used the Probability Sampling method in the Simple Random Sampling section for class VIII 4 as the experimental class and class VIII 1 as the control class. The data collection technique in this study was a test of students' ability to understand mathematical concepts. The analysi stechnique in this study uses the t- test as a hypothesis test. Based on the t- test, the results are high > table or 6,827 > 2,001, and sig - 0.000 < 0.05 with (df) n-2, the decision taken by Ho is rejected and Hy is accepted. So it can be concluded that the ability to understand mathematical concepts of students with using the LKS- assisted discovery learning model is better than the ability to understand students' mathematical concepts using conventional learning models.Keywords: Discovery learning, Student Worksheets (LKS), Understanding of mathematical concepts